FORMATION OF CROSS-CULTURAL COMPETENCE OF FOREIGN STUDENTS IN THE PROCESS OF LEARNING UKRAINIAN AS A FOREIGN LANGUAGE - Галина Дідук-Ступ'як (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article is devoted to the problem of formation of cross-cultural competence of foreign students in the process of learning Ukrainian as a foreign language. Theoretical and pragmatic ways of intercultural communication methods for speakers of a foreign language in four types of speech activity have been substantiated. There have been determined linguistic and didactic principles of learning the Ukrainian language as a foreign language using authorial technology of interaction of different approaches that promotes the development of effective cross-cultural competence of foreign students. The main components of the innovative technology of work with foreign language audience have been characterized; a system of tasks and exercises aimed at mastering linguistic, socio-cultural and pragmatic competences has been set. There have been determined linguistic and methodical problems of comparative methodology, which authoring technology LTIRP with the usage of authentic texts is based on. Traditional and new forms, methods and techniques of teaching foreign students in the process of formation of cross-cultural competence have been considered.